Economic Development in Emerging Asian Markets : Implications for Europe - Martin, Will; Ianchovichina, Elena; Dimaranan, Betina (2012)
The impacts of faster growth in China and India for Europe are analysed taking into account terms-of-trade effects, second-best welfare impacts and improvements in product quality and variety. More rapid growth in these giants could improve Europe's terms of trade, but second-best effects on energy markets could lower welfare unless these taxes are Pigovian. Whether growth arises from productivity or capital accumulation has important implications, with capital-driven growth involving higher energy and agricultural prices. When quality and variety growth are taken into account, the benefits to Europe are substantially greater. If agricultural protection in emerging Asia increases with growth, the impacts on Europe appear to be adverse but small.